2002
DOI: 10.1074/jbc.m112207200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of PKCα Activity by C1-C2 Domain Interactions

Abstract: In this study, the role of interdomain interactions involving the C1 and C2 domains in the mechanism of activation of PKC was investigated. Using an in vitro assay containing only purified recombinant proteins and the phorbol ester, 4␤-12-O-tetradecanoylphorbol-13-acetate (TPA), but lacking lipids, it was found that PKC␣ bound specifically, and with high affinity, to a ␣C1A-C1B fusion protein of the same isozyme. The ␣C1A-C1B domain also potently activated the isozyme in a phorbol ester-and diacylglycerol-depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
73
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 55 publications
9
73
1
Order By: Relevance
“…Although the SCA14 mutations in the C1B subdomain showed similar kinetics and conformational changes as modification or deletion of the upstream V1-domain, they could also affect functioning of the other regulatory domain, the C2 domain (Oancea and Meyer, 1998;Slater et al, 2002;Stahelin et al, 2005;Stensman et al, 2004). However, we did not observe any effect of the SCA14 mutations on C2 functioning as measured by PKCγ calcium sensitivity (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…Although the SCA14 mutations in the C1B subdomain showed similar kinetics and conformational changes as modification or deletion of the upstream V1-domain, they could also affect functioning of the other regulatory domain, the C2 domain (Oancea and Meyer, 1998;Slater et al, 2002;Stahelin et al, 2005;Stensman et al, 2004). However, we did not observe any effect of the SCA14 mutations on C2 functioning as measured by PKCγ calcium sensitivity (Fig.…”
Section: Discussioncontrasting
confidence: 47%
“…This may also be the case for ⑀PKC. Recently Stubbs and co-workers (40) have demonstrated that in ␣PKC there is also an additional intramolecular interaction between the C1 and C2 domains that maintains the enzyme in its inactive state. In addition, they have suggested that ␣PKC forms dimers through an intermolecular interaction between the C1 and C2 domains, we cannot reject the hypothesis that this is also the case for the ⑀RACK-binding site and the ⑀RACK (40).…”
Section: Mathematical Modeling Of ⑀Pkc Translocation Suggests That ⑀Pmentioning
confidence: 99%
“…Although the C1 domains of Apl I and Apl II bind phorbol esters to a similar extent , this does not necessarily predict affinities for DOG (Slater et al, 1996). Alternatively, because the availability of the C1 domain to DAG is restricted by the C2 domain Medkova and Cho, 1999;Slater et al, 2002), calcium may be required for access of DAG to the C1 domain in Apl I, whereas cofactors that allow access are either not required for Apl II, or are already present in cells.…”
Section: Differential Translocation Of Apl I and Apl Iimentioning
confidence: 99%